Memahami al-Qur’an dengan Kearifan Lokal: Nuansa Budaya Sunda dalam Tafsir al-Qur’an berbahasa Sunda - Jajang A Rohmana (Qur'an and Hadith Academic Society, 2014)
The local interpretation of the Qur’an cannot be ignored in the discourse of Qur’anic studies in Indonesia. Its significance lays not only in the continuity of Islamic tradition networks, but also in the creativity of linguistic expression and its content of local wisdom relevant with the need of society. This study tries to shed light on the Sundanese cultural nuance in Sundanese Qur’anic interpretation. There are at least three elements which indicate Sundanese cultural nuance which becomes the characteristic of local reception of the Qur’an in Sundanese Qur’anic interpretation: the use of speech level, traditional expression and the metaphore of Sundanese nature. These three elements can be used as the first categorization to classify Sundanese Qur’anic interpretation as Sundanese.